UKRAINE, RUSSIA, AND THE CENTRAL ASIAN STATES: OOPERATION PROBLEMS IN THE GAS SECTOR - PREIGER, David; MALIARCHUK, Irina; GRINKEVICH, Taisia (CENTRAL ASIA AND THE CAUCASUS, 2004)
Ukraine is a country that does not have enough oil and gas resources, its raw hydrocarbon consumption level is much higher than its production level, and the country must look for ways to compensate for this difference in a situation where it clearly does not have the funds to do so. On the bright side, the republic is in an advantageous geographic location between the oil- and natural gas-rich Russian Federation (this country links it by transit with Kazakhstan, and through it with Uzbekistan and Turkmenistan) and the large consumers of these resources in the West—the countries of East, Central, and West Europe, the Balkan states, and even Turkey. Together with the significant extractable resources of oil and gas available in Ukraine as early as the middle of the last century, its position was conducive to building large oil and gas pipelines for delivering Ukrainian raw material to other republics of the U.S.S.R.Belarus, Lithuania, Latvia, Estonia, and Russia) at the end of the 1940s, and then (after the most accessible resources were extracted) they were used to export the Russian Federation’s hydrocarbons in the western and southwestern directions.